HUBUNGAN PENGETAHUAN DAN PERSONAL HYGIENE DENGAN LEUKORRHEA PADA SISWI SMA NEGERI 3 PALEMBANG - Ririn Anggraini (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2012)
Adolescence is a stage between childhood and adulthood. At this time there is an increase in hormones that have side effects, especially the increase in the hormone estrogen in women who can cause leukorrhea (BKKBN, 2001). According to the World Health Organization (WHO), vaginitis affects nearly 75% of women during their lifetime and about 40-50% of cases of recurrence. Meanwhile, according to BKKBN in 2004 also states that 75% of women in the world at least once experienced a whiteness in his life. In addition, according to Elistiawaty in 2006, 75% of women experience whiteness once in their life. The purpose of this study was to determine the relationship between knowledge and personal hygiene with leukorrhea incidence in female students in SMA Negeri 3 Palembang in 2009. The design of this study is an analytical survey with cross sectional approach. The population of this study is all students of class X and class XI amounted to 351 people and the sampling technique is Simple Random Sampling using Notoadmodjo formula so that the sample of 78 respondents. Each of the variables studied was tested by using statistical test of Chi Square. The results showed that 78 respondents found that leukorrhea experienced 41.0%, respondents with less knowledge of 75.6% and respondents with personal hygiene less by 65.4%. Statistical test result with ρ value = 0,005 <0,05 on knowledge and ρ value = 0,007 <0,05 on personal hygiene. Conclusion There was a significant correlation between knowledge with leukorrhea incidence (p value = 0,005 <0,05) and there was significant relation between personal hygiene and leukorrhea incidence (p value = 0,007 <0,05). Suggestion for high school students 3 Palembang to further improve the knowledge and always maintain the outer genital hygiene, so that leukorrhea events can be avoided.